Crystal structure of catena-poly[tetrakis(butyl)-μ2-2-((oxido(phenyl)methylene)hydrazineylidene)propanoato-κ4 O:O,O′,N-μ2-2-((oxido(phenyl)methylene)hydrazineylidene)propanoato-κ4 O,N,O′:N′-ditin(IV)], C34H50N6O6Sn2 - Gao Zhongjun; Zhang Haifeng (Zeitschrift für Kristallographie - New Crystal Structures)
C34H50N6O6Sn2, triclinic, P 1‾ $\overline{1}$ , a = 12.110(2) Å, b = 12.406(2) Å, c = 13.744(3) Å, α = 79.547(2)° $79.547(2){}^{°}$ , β = 82.072(2)° $82.072(2){}^{°}$ , γ = 87.257(2)° $87.257(2){}^{°}$ , V = 2010.7(7) Å3, Z = 2, R gt(F) = 0.0471, wR ref(F 2) = 0.1392, T = 298 K.